Perspectives for Implementation of New Variative Modulesof «Physical Culture. Grades 5–9» Training Program - Belikova, Natalia; Indyka, Svitlana; Ulyanytska, Natalia; Podubinska, Svitlana; Krendelieva, Venera (Волинський національний університет імені Лесі Українки, 2017)
Today, the Ukrainian school is on the verge of profound educational reforms. A significant step towards a new Ukrainian school is to update the programs of the main school, taking into account the competence approach. The study of the prospects for the introduction of new variable modules of the educational program «Physical Culture. Grades 5–9» requires a detailed analysis to improve the physical education of pupils. The history of the formation of new types of sports for physical education lessons and the state of their current development in Ukraine are described. Among them: rugby, korfball, pétanque, fencing, military sports games, step aerobics and cheerleading. The attitude of teachers of physical education to the possibilities of introducing new variable modules is researched. The interests of pupils and their interest in their learning were studied. The analysis and summary of literary sources, questioning-diagnostic and mathematical-statistical methods are used. A survey of teachers of physical education of middle grades (36 people) and pupils of grades 5–9 (120 people) of secondary schools of Lutsk was conducted. It has been established that 56,25 % of the pupils would like to diversify physical education lessons because they are not always interesting (46,25 %). 20 % of the teachers do not always take into account the interests of their pupils when planning physical education lessons. Among the kinds of sport that arouse the greatest interest of the teachers and the material and technical possibilities for their implementation are: step aerobics (50 vs. 40 %), military-sports games (20 vs. 5 %), cheerleading (15 vs. 10 %) and rugby (10 versus 15 %). Pupils showed a desire to study military-sports games (38,75 %), rugby, step aerobics, fencing (28,75, 27,75 and 27,5% respectively) and cheerleading (23,75 %). Korfball, pétanque and fencing are not of interest to any of the teachers; pétanque and korfball arouse the lowest interest among the pupils. During the courses of higher education in institutes of postgraduate pedagogical education it is offered to introduce special courses on the main innovations taking into account peculiarities and traditions in the development of physical education in a particular region.
Keywords: curriculum; pupils; physical education; new variational modules; teachers; 796.011.3